2021
DOI: 10.1177/15579883211022180
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Impacts of the COVID-19 Pandemic on Relationship Satisfaction in Male Couples

Abstract: Little is known about the impact of the coronavirus pandemic and control measures on gay, bisexual, and other men who have sex with men (GBMSM) couples. The goal of this study was to investigate individual-level relationship satisfaction during the COVID-19 pandemic in a sample of 209 coupled GBMSM in the United States. We analyzed reported happiness and feelings about a relationship’s future and assessed the odds of changing relationship happiness and investment associated with pandemic-related life changes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…For example, an increase in communication, social integration, and social cohesion was observed in families coping with hardship during the pandemic [ 76 ]. People reported spending more time with family and loved ones and had become more invested in the relationship, increasing sexual behavior and relationship happiness [ 17 ]. Many people also found time to develop their interests and learn new skills, provide a more active and healthier lifestyle, and develop interests, art activities, and hobbies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an increase in communication, social integration, and social cohesion was observed in families coping with hardship during the pandemic [ 76 ]. People reported spending more time with family and loved ones and had become more invested in the relationship, increasing sexual behavior and relationship happiness [ 17 ]. Many people also found time to develop their interests and learn new skills, provide a more active and healthier lifestyle, and develop interests, art activities, and hobbies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al [ 14 ] suggested that the adverse consequences of lockdown can affect mentally and physically quarantined individuals and the whole healthcare system. Meanwhile, the pandemic has not only shown a negative impact on human life but plenty of positive effects of the lockdown were reported among people around the world, including spending more time with other people, improved communication and greater investment in family life, more free time for entertainment and relaxation, development of interests and hobbies, and increased creativity and technological innovation [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In countries like India, only a few big organizations can provide the faculty of work from home for employees. Most of the companies are not even prepared [82]. Corona outbreaks show that companies should focus on implementing WFH more as it saves electricity and decreases carbon emissions in nature.…”
Section: Positive Impacts On Covid-19mentioning
confidence: 99%
“…However, other studies showed that satisfaction remained stable during the first weeks of the pandemic and that people blamed their partners less, preferring not to attribute their negative behaviors to their internal characteristics [26]. Others found no association between quarantine and marital satisfaction, in both heterosexual and gay and lesbian couples [27,28]. Higher marital satisfaction was related to a lower impact of confinement on health, physical and emotional well-being [29].…”
Section: Adult Romantic Relationshipsmentioning
confidence: 99%